Analysis of the Biophysical Conditions of Type A Tidal Swamp on Production Results and the Development of Siam Pandak Rice Farming in Barito Kuala Regency - Zulipah Mahdalena; Muhammad Rifky Aditya (Universitas Pendidikan Mandalika, 2025)
This study aims to evaluate the biophysical conditions of Type A tidal swamp lands in Barito Kuala Regency, South Kalimantan, and their impact on the productivity and economic sustainability of Siam Pandak rice farming. The biophysical data collected revealed that the soil conditions in the study area have a pH ranging from 4.5 to 5.0 (acidic), organic matter content ranging from 2.5% to 3.5%, and total nitrogen content between 0.18% and 0.25%. Average phosphorus availability was between 8 and 12 ppm, with potassium levels measured at 0.25 to 0.40 cmol/kg. Although the soil pH is low, leading to high solubility of toxic metals such as iron (Fe) and aluminum (Al), lime application (liming) can increase soil pH to more neutral levels, reducing Fe/Al toxicity, which in turn improves nutrient availability and supports rice growth. In terms of plant growth, the average height of Siam Pandak rice plants reached 135–150 cm, with 12 to 18 productive tillers per hill. Rice productivity was 3.5–4.5 tons of dry harvested grain (GKG) per hectare, which is still below the maximum potential (5–6 tons/ha). Regression analysis showed that soil pH, organic matter content, and potassium availability had a positive effect on productivity, while Fe/Al toxicity showed a significant negative effect. Effective water management strategies, including the alternating wetting and drying (AWD) system and proper drainage, helped reduce waterlogging risks and enhanced root growth. Economically, farmers who implemented effective soil and water management practices recorded a significant increase in net income, with an average income of IDR 33,968,750 per farmer per planting season. These findings emphasize that the application of proper soil amendments, good water management, and optimal biophysical conditions can increase rice yields and the economic sustainability of Siam Pandak rice farming in tidal swamp areas.